2011
DOI: 10.1007/s11090-011-9319-y
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanoparticle Production by Inductively Coupled Thermal Plasmas: Controlling the Thermal History of Particle Nucleation

Abstract: The process control for reproducibility, uniformity, and achievement of desired structures for carbon black generated in thermal plasma devices is studied in this paper through modeling, and correlated with experimental results. A numerical simulation of the flow and energy fields, stream function lines and the quench rates of the plasma gas in a conical shape reactor at different pressures was made. An argon plasma is used with highly diluted methane (0.6-7%) as the carbon precursor. The quench rates were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Their research revealed that factors influencing graphene flakes synthesis include the precursor type, reactor design, flow rate of buffer gas, etc. Pristavita et al [23][24][25][26][27][28] and Cheng et al [29] developed a radio-frequency plasma system for graphene flakes synthesis via methane decomposition. Their study indicated that a high reaction temperature and addition of H 2 may promote the transformation of products from spherical particles to graphene flakes.…”
Section: Introductionmentioning
confidence: 99%
“…Their research revealed that factors influencing graphene flakes synthesis include the precursor type, reactor design, flow rate of buffer gas, etc. Pristavita et al [23][24][25][26][27][28] and Cheng et al [29] developed a radio-frequency plasma system for graphene flakes synthesis via methane decomposition. Their study indicated that a high reaction temperature and addition of H 2 may promote the transformation of products from spherical particles to graphene flakes.…”
Section: Introductionmentioning
confidence: 99%
“…After the temperature in the near region is slightly lowered, carbon atoms will combine with each other to form carbon fragments, such as C 2 , C 3 , and so on, followed by nucleation. 44 Pristavita et al 45 reported that the nucleation temperature of graphene is 3000-5000 K, while 2500 K is obtained by Chen et al 46 through dynamic simulation. When the temperature further away from the central area of the arc is lower, graphene will continue to grow under the attack of carbon fragments and will form graphene flakes in the end.…”
Section: Equipment and Growth Mechanismmentioning
confidence: 99%
“…Similar to RF, inductively coupled plasma (ICP) can be used for free-standing graphene production with higher power under a pressure below 1 atm. 45,71,72 Mohanta et al 71 carried out the study in inductively coupled Ar/H 2 plasma at a power of 15 kW and a pressure of 400 mbar and found that the temperature of pure Ar plasma reached ∼6050 K, while the temperature of the plasma dropped to ∼4210 K after H 2 introduction (Figures 7e and 7f). This was attributed to the inhibition of vibrationally excited H 2 molecules to the ionization of Ar, which was also reported by Sun et al 21 Legrand et al 72 also used ICP to prepare graphene using CH 4 under 20-25 kW and 13-56 kPa, in which the temperature was 6500-7500 K. It was found that the layers of graphene were 5-20 with a I D /I G ranging from 0.3 to 0.4.…”
Section: Radio Frequency-induced Thermal Plasmamentioning
confidence: 99%
“…However, the relevant study has been plagued by extreme synthesis conditions such as high temperature and its strong gradient, and thus still remains elusive. In the previous study of graphene synthesis by an induction thermal plasma, Pristavita et al reported that the absence of recirculation eddies at the entrance of the reactor greatly improves uniformity in the particle size distribution and also suppresses the production of volatile compound impurities. , Based on numerical simulation, they suggested that the long residence time of the particles trapped in the colder recirculation zones is responsible for the formation of volatile compounds. A geometry that eliminates recirculation eddies was proved to completely eliminate such impurities in the product.…”
Section: Introductionmentioning
confidence: 99%